Application of MCDM for Estimating Student Performance in University English Translation Courses under IndetermSoft Set - Qin Xu (Neutrosophic Sets and Systems)
Evaluating student performance in university English translation courses is a complex process that requires a comprehensive assessment of multiple factors. Traditional assessment methods often fail to capture the nuances of translation quality, linguistic proficiency, and contextual adaptation. The application of Multi-Criteria Decision-Making (MCDM) methodologies offers a structured and systematic approach to estimating student performance based on diverse and interdependent criteria. By integrating MCDM, universities can develop a more objective, data-driven framework for evaluating translation skills while ensuring fair and consistent grading practices. This study uses two MCDM methods such as CRITIC method to compute the criteria weights and the RAFSI method to rank the alternatives. We use the IndetermSoft set to deal with indeterminacy in the values of the criteria. These methods are applied into a case study with eight criteria and seven alternatives.